TEACHER PERCEPTION TOWARDS THE DEVELOPMENT OF MATHEMATICS MATERIALS BASED ON PAPUAN LOCAL WISDOM TO IMPROVE NUMERACY SKILLS OF JUNIOR HIGH SCHOOL STUDENTS IN CENTRAL PAPUA PROVINCE - Ebit Rusali; Muhammad Arysad; Nurhikmah (RADJA PUBLIKA, 2025)
This research aims to analyze teachers' perceptions of the development of mathematics materials based on Papuan local wisdom in enhancing numeracy skills among junior high school students. The integration of local wisdom in mathematics learning becomes an important strategy for creating meaningful and contextual learning experiences. The research methodology employed a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and questionnaires administered to mathematics teachers in junior high schools across Papua. Research subjects include mathematics teachers with a minimum of three years teaching experience who have implemented culturally-based learning approaches. Data analysis was conducted using triangulation techniques to ensure the validity and reliability of research findings. The results demonstrate that teachers maintain positive perceptions toward the development of mathematics materials based on Papuan local wisdom, with indicators including increased student learning motivation, enhanced conceptual understanding, and improved relevance of learning to daily life experiences. The implementation of local wisdom in mathematics materials proves effective in improving students' numeracy skills through learning approaches that accommodate local cultural values. These findings contribute significantly to the development of more contextual and meaningful mathematics learning strategies for students in the Papua region, providing valuable insights for educational stakeholders seeking to bridge cultural heritage with academic excellence.